Interlocking Liquid Containers as Makeshift Shelter for Disaster-affected Communities and Non-load Bearing Walls for Buildings - Balante, Clarissa M.; Lejano, Charles A.; Panaligan, Charmaine Majel A. (Journal in Urban and Regional Planning, 2022)
During natural calamities, evacuation centers provide temporary shelters for affected communities. While these facilities provide a haven for the victims, they also engender a host of problems such as lack of privacy, discomfort, the spread of diseases, exposure of women and lactating mothers, and absence of boundaries, among others. These problems can be solved by developing a new geometric design for liquid containers, specifically PET bottles, characterized by an interlocking feature. This feature allows PET bottles to be assembled as makeshift shelters for the victims since each bottle is designed to be a component of modular panels that can function as temporary walls for emergency shelters. The design of the bottle is standard for half a liter, 1.0 liter, and 1.5-liter plastic containers. This design is beneficial to government agencies tasked to respond to natural calamities by improving the physical and social conditions of the victims in evacuation centers. It also reduces the accumulation of non-biodegradable wastes and introduces readily-available but innovative materials to achieve sustainable infrastructure. Keywords: Interlocking, makeshift, modular, emergency shelter, building material